2020
DOI: 10.5194/egusphere-egu2020-19425
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Changing atmospheric acidity as a modulator of nutrient deposition and ocean biogeochemistry

Abstract: <p>Anthropogenic emissions of nitrogen and sulphur oxides and ammonia have altered the pH of aerosol, cloud water and precipitation, with significant decreases over much of the marine atmosphere. Some of these emissions have led to an increased atmospheric burden of reactive nitrogen and its deposition to ocean ecosystems. Changes in acidity in the atmosphere also have indirect effects on the supply of labile nutrients to the ocean. For nitrogen, these changes are caused by shifts in the chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 2 publications
0
14
0
Order By: Relevance
“…Analysis of aerosols collected in southern Tasmania, Australia, in December and January, showed that the wildfire emissions were associated with elevated concentrations of soluble iron (Perron et al., 2022). Iron emitted during the wildfires was predominantly contained in soil particles entrained in the fire plumes by pyro‐convective winds (Bodí et al., 2014; Wagner et al., 2018) and processed by the heat and acidity of the fire fumes (Baker et al., 2021; Balasubramanian et al., 1999; Perron et al., 2022). Pyro‐convective updraft of soil may account for more than 60% of the pyrogenic iron emitted during wildfires (Hamilton et al., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of aerosols collected in southern Tasmania, Australia, in December and January, showed that the wildfire emissions were associated with elevated concentrations of soluble iron (Perron et al., 2022). Iron emitted during the wildfires was predominantly contained in soil particles entrained in the fire plumes by pyro‐convective winds (Bodí et al., 2014; Wagner et al., 2018) and processed by the heat and acidity of the fire fumes (Baker et al., 2021; Balasubramanian et al., 1999; Perron et al., 2022). Pyro‐convective updraft of soil may account for more than 60% of the pyrogenic iron emitted during wildfires (Hamilton et al., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that proton‐promoted dissolution (i.e., acid processing) could substantially enhance aerosol Fe solubility (Baker et al., 2021; Chen & Grassian, 2013; Cwiertny et al., 2008; Ito & Feng, 2010; Li et al., 2017; Meskhidze et al., 2003; Scanza et al., 2018; Shi et al., 2012, 2015). Molar ratios of acidic species to total Fe were widely used in previous work (Liu et al., 2021; Shi et al., 2020; Zhu et al., 2020) to represent the relative degree of acid processing of aerosol Fe, and this method was also adopted in our work.…”
Section: Discussionmentioning
confidence: 99%
“…Aerosol Fe solubility was frequently observed to increase with decrease in total aerosol Fe (Baker & Jickells, 2006; Sholkovitz et al., 2012), and several mechanisms have been proposed to explain the observed variability of aerosol Fe solubility (Baker et al., 2021; Ito et al., 2019; Mahowald et al., 2018; Meskhidze et al., 2003). One mechanism is physical sorting (Baker & Jickells, 2006), that is, preferential deposition of coarser dust particles with lower Fe solubility leads to increase in relative contribution of finer particles with higher Fe solubility, though a later study (Shi, Woodhouse, et al., 2011) suggested that this effect was small.…”
Section: Introductionmentioning
confidence: 99%
“…Primary production on the ocean surface is limited by the depletion of dissolved iron (Fe, Martin and Fitzwater, 1988;Jickells et al, 2005;Baker et al, 2016Baker et al, , 2021Mahowald et al, 2018;Meskhidze et al, 2019). The fertilization of Fe in the surface ocean has the potential to regulate global climate systems through the uptake of atmospheric carbon dioxide (CO 2 ) in surface seawater.…”
Section: Introductionmentioning
confidence: 99%
“…Dissolved Fe must be supplied to activate biological activity because microorganisms utilize dissolved Fe as a micronutrient (Boyd et al, 2007;Moore et al, 2013;Mahowald et al, 2018). Atmospheric deposition of Fe in mineral dust is a dominant source of dissolved Fe on the ocean surface (Jickells et al, 2005;Baker et al, 2016Baker et al, , 2021Mahowald et al, 2018;Meskhidze et al, 2019). However, fractional Fe solubility (Fe sol % = (labile Fe / total Fe) × 100) in mineral dust in source regions is usually below 1.0 % because Fe in mineral dust is typically present as insoluble species, e.g., Fe in aluminosilicates and Fe (hydr)oxides.…”
Section: Introductionmentioning
confidence: 99%